Prostitution and Its Impact on Youth: Violence, Domination and Inequality. Issue 2 (December 2017) - Pape, Pierrette
While the debates on prostitution usually focus on the different legislative approaches or the so-called choices of persons in prostitution, this article wants to give light to an invisible aspect of the system of prostitution: its impact on youth. Through research, data and facts, we want to show that it is urgent to listen to young women's voices as they are detrimentally affected by an industry based on violence, domination and inequality. Based on a study conducted on young people in the South of France, at the borders with Spanish prostitution clubs, outcomes and analysis clearly demonstrate that prostitution is not only a form of male violence against women, it is also a system and an industry that contribute to gender inequality, to an unequal and negative representation of sexuality for young people, and to reduced choices in sexuality. Its impacts are far more detrimental than we can see, because they are invisible and entrenched in mentalities. Today, young people, and especially young women, are directly targeted by the system of prostitution. Rape culture, economic conditions, migration paths and sexual violence in the childhood are part of the root causes which explain the highest vulnerability of youth to the sex industry. Youth has become a strong commercial value for the sex industry and for the men buying sex; the sex industry does not discriminate on age and uses the existing laws tolerating pimping and prostitution to continue to flourish. The article points out that despite the politically correct trend which supports a neo-liberal approach to prostitution, young people are taking a stance against the sex industry and are strongly supporting the Nordic model approach; this raises an important question—Are we ready to listen to them?